Spatial distribution of Vespa affinis based on land use and population density in Bojonegoro District, East Java Province, Indonesia - Laily Agustina Rahmawati; Dewi Hidayati; Dian Saptarini; Mrabawani Insan Rendra; Bella Lutfiani Al Zakina (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rahmawati LA, Hidayati D, Saptarini D, Rendra MI, Al Zakina BL. 2023. Spatial distribution of Vespa affinis based on land use and population density in Bojonegoro District, East Java Province, Indonesia. Biodiversitas 24: 861-868. Cases of Vespa affinis (Lesser banded hornet) attacks significantly increased last three years in several regions in Indonesia, including Bojonegoro District, East Java Province. Based on the Evacuation Report data from the Fire Department of Bojonegoro District, the number of Nest Evacuations increased nine times from 2019 to 2021. Even the Vespa Wasp attack caused one person to die. This study's purpose is to analyze the distribution and habitat characteristics of Vespa Wasps in Bojonegoro based on land use and population density. The method used a survey of Vespa wasp evacuation points to see the distribution in each area, the results were covered on the land use map and population density map in Bojonegoro in 2021. The results showed that the distribution of V. affinis wasps based on land use has an 83% tendency to be in residential areas, while based on population density, it shows that 87% of the nests are in areas with high population density. The tendency of the wasps to inhabit residential areas with high population density is likely to be an adaptive form of wasp in response to forest destruction as its natural habitat, so they seek more abundant food sources and safer nesting locations in new places.